No Compromise — No Political Trading: The Marxian Socialist Tradition in British Columbia - Johnson, Ross Alfred (University of British Columbia, 1975)
At the turn of the century, socialist groups of several different hues were active in British Columbia. Out of this variegated skein emerged the Socialist Party of Canada. For almost two decades it dominated left-wing politics in B.C., wielding extensive power in the labour movement and leaving behind it an ideological legacy which eventually filtered into the fledgling CCF. This study documents the conditions which led to the SPC's ascendancy, discusses its relationship with the early labour movement and examines the extent of Marxist influence on later socialist developments in the province. The dissertation employs an historical approach, supplementing library resources with correspondence and interviews with members of the old SPC. When reformist attempts of the late nineteenth century failed to improve conditions for the B.C. worker, labourism lost out to radicalism. The SPC was national in name only, for its doctrinaire Marxism evoked a significant response only in the unique political, industrial and social milieu of British Columbia. The rapid resource exploitation which gave rise to empires early in the province's history created a classical Marxist situation in some areas. The absence of party alignments in the early years of socialist activity, plus a following of radical immigrants from Britain, the U.S., and eastern Canada afforded the Marxists a large audience to which they addressed themselves with tireless propaganda efforts. Many SPC members were active in the labour movement as well, and were able to prevent the formation of a labour party for many years. When other parties finally did form with labour support, they were much farther to the left than were earlier labour parties. In large part this was due to the ambitious education program which characterized the socialist movement from its inception and ultimately became the Marxist's chief raison d'etre. Candidates were run solely for educational purposes. Once elected, however, SPC legislators found themselves in a balance of power position for a time and consequently their legislative accomplishments were considerable. The failure to adapt to Marxist theory to changing B.C. circumstances ultimately cost the Party credibility. Unable to withstand internal pressures or to respond to the political challenges of World War I, inflation, conscription, labour unrest, and the Russian Revolution, the SPC was gradually replaced by other groups on the left. However, the Party's adherence to a one-plank no-compromise platform did preserve the Marxist ideal in the province for later socialist groups.